MUCHALINDA: THE SERPENT KING IN BUDDHIST MYTHOLOGY - Bhoi, Kamala Kant; Bhoi, Chandrika; Barik, Alfa Anupama Priyadarshini; Barik, Shreekant (International Journal of Research -GRANTHAALAYAH, 2024)
Muchalinda, the serpent king, is a significant figure in Buddhist mythology, known for protecting Gautama Buddha from the evils after his enlightenment. This article explores the development of Muchalinda's character, his artistic representations, and the archaeological significance of the Muchalinda image discovered in Ganiapali, Odisha. The article highlights the importance of Muchalinda in Buddhist art and culture, and sheds light on the history and cultural heritage of Odisha.